F/Actual knowing: putting facts and values in place - Rolston, Holmes, 1932-2025, author; Indiana University Press, publisher (Colorado State University. Libraries, 2005)
Knowing needs to be actualized, an act of ours, yet also a discovery of what is actually, factually there. Embodied, emplaced persons, shaped by our concepts and percepts, perhaps all our knowledge wears a human face. But we humans have powers of dis-placement too, sometimes taking up the situations of others than humans. Language is for conversing with each other; language is for encountering the world we inhabit. We sometimes find placed there before us what we variously value on Earth. The human genius can transcend location.
Theme issue on Epistemology and Environmental Philosophy.
Keywords: nature; ecology; knowledge; environmental values; perceptual experience; green; epistemology